Meat me halfway: Sydney meat-loving men’s restaurant experience with alternative plant-based proteins - Bogueva, Diana; Marinova, Dora; Bryant, Christopher (MDPI AG, 2022)
Within the theoretical framework of psychological reactance and impression management, this study conducted in Sydney, Australia, in 2020–2021, explores the acceptance by men of alternatives to animal-based foods. Qualitative in-depth interviews were conducted with 36 men who have visited a vegan restaurant and have eaten a plant-based burger. The findings from the study show that, despite the increasing popularity of these novel food options, men are unlikely to include the plant-based alternatives as a permanent feature of their diets as explained by the theory of psychological reactance. However, the study’s male participants acknowledged the importance of women for their visit to the vegan restaurant which can be explained by impression management theory. Using excerpts from the interviews, men’s experience is highlighted, particularly as it relates to concerns linked to masculinity, dietary identity and social perception by others. The analysis reveals the complexity of transitioning to more sustainable food choices within a gender-constructed social environment. Whether the new plant-based alternatives to meat are going to be a short-lived trend or a more lasting option in the men’s diets is also discussed. Practical implications for social marketing as a tool to influence collective behaviour are drawn. They emphasise the role of women, changing social perceptions and transparency about the new plant-based products.